Separate vertical wiring versus conventional tension band fixation for inferior pole patellar fractures: a prospective cohort study on postoperative patella baja and functional outcomes - Yanchun Gao; Shichang Zhao; Xingang Yu; Yun Qian; Dehao Fu (Journal of Orthopaedic Surgery and Research)
Abstract Objective To compare the clinical efficacy of the separate vertical wiring (SVW) technique and conventional tension band fixation in managing AO/OTA type A1 inferior pole patellar fractures, focusing on postoperative patella baja incidence and functional recovery. Methods From January 2019 to January 2023, 242 patients with AO/OTA A1 inferior pole patellar fractures undergoing surgical treatment were assigned to the SVW group (n = 117) or tension band (TB) group (n = 125). The primary outcome was the incidence of patella baja (Insall-Salvati index < 0.8) at the 12-month follow-up. Secondary outcomes included knee range of motion (ROM), Böstman functional score, and complications. Results The SVW group demonstrated a significantly lower incidence of patella baja compared to the TB group (25.6% vs. 52.1%, P < 0.001), with higher mean (Insall-Salvati index) ISI values (0.87 ± 0.16 vs. 0.76 ± 0.12, P < 0.01). Knee ROM was superior in the SVW group (124.0°±14.2° vs. 119.9°±12.4°, P = 0.017), though no significant difference was observed in Böstman scores (25.1 ± 3.5 vs. 24.6 ± 3.6, P = 0.33). The overall complication rate was 5.8% (14/242), primarily comprising surgical site infections (3.5%, 8/242: 1.2% superficial, 2.1% deep), fixation failure (1.2%, 3/242), and nonunion (0.8%, 2/242). Notably, soft tissue irritation occurred exclusively in the TB group (8.8%, 11/125 vs. 0% in SVW; P = 0.005). Conclusion The SVW technique significantly reduces the risk of patella baja and improves knee range of motion by optimizing vertical tension distribution, establishing it as a biomechanically superior fixation strategy for AO/OTA A1 inferior pole patellar fractures. These findings support SVW as a first-line treatment for such complex injuries.